Spelling bee: My personal experience (Ideoscopio, 2025)
This narrative text recounts the author's experience in an inter-university spelling competition organized by the Catholic University in November 2023. Four students from the Spanish and English degree program represented the university at levels A2 and B1. It describes all the challenges they faced, the confusion, and the shared joys. The author concludes this text by inviting readers to participate in this type of enriching experience beyond the competition.